The Influence of Content Richness, Perceived Ease of Use, and Perceived Usefulness on the Use of Iflix Application in Indonesia - Anggriani Harini; V. Dicko Marcello; M. Rafi Juniko Putra; Andre A. Prabowo; La Mani; Z. Hidayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
An alternative channel for watching cinema film entertainment is the online channel which is growing rapidly. Cinema media consumer behavior has shifted along with the generation of its users. This study aims to examine the effect of Content Richness, Perceived Ease of Use, and Perceived Usefulness on the use of the Iflix application in Indonesia. A quantitative approach with a survey methodology was carried out to 422 respondents following the official Iflix Indonesia social media. Data processing was carried out using SEM-PLS to test various relationships between variables. The most significant number of Iflix application users are in the age group <= 17 years and <= 25 years, with 55.9% of respondents in the female gender group. The level of education of respondents ranged from high school graduates 60.2%, and 50.7% bachelor degree. Meanwhile, some of the respondents were students 50.5% and the rest were employees. It was found that the effect of Perceived Ease of Use has a significant and positive influence on users of the Iflix application with a score of 7.211. It can be concluded that Content Richness, Perceived Ease of Use, and Perceived Usefulness have a positive and significant effect on users of the Iflix application.